Peripheral skeleton bone strength is positively correlated with total and dairy protein intakes in healthy postmenopausal women. Issue 2 (11th January 2017) - Durosier-Izart, Claire; Biver, Emmanuel; Merminod, Fanny; van Rietbergen, Bert; Chevalley, Thierry; Herrmann, François R; Ferrari, Serge L; Rizzoli, René
ABSTRACT: Background: Bone mineral content (BMC) and bone mineral density (BMD) are positively correlated with dietary protein intakes, which account for 1–8% of BMC and BMD variances. However, the relation between bone strength and microstructure, which are variables that are not captured by areal bone mineral density (aBMD), and dietary protein intakes, particularly from specific dietary sources, has not been clearly established. Objective: We investigated the association between the peripheral skeleton–predicted failure load and stiffness, bone microstructure, and dietary protein intakes from various origins (animal, divided into dairy and nondairy, and vegetable origins) in healthy postmenopausal women. Design: In a cross-sectional study in 746 Caucasian women aged 65.0 ± 1.4 y, we measured the aBMD with the use of dual-energy X-ray absorptiometry, the distal radius and tibia bone microstructures with the use of high-resolution peripheral quantitative computerized tomography, and bone strength with the use of a finite element analysis, and we evaluated dietary protein and calcium with the use of a validated food-frequency questionnaire. Results: Mean dietary calcium and protein intakes were greater than recommended amounts for this class of age. The predicted failure load and stiffness at the distal radius and tibia were positively associated with total, animal, and dairy protein intakes but not with vegetable protein intake. Failure load differences were accompanied by modifications of the aBMD and of cortical and trabecular bone microstructures. The associations remained statistically significant after adjustment for weight, height, physical activity, menopause duration, calcium intake, and the interaction between calcium and protein intake. A principal component analysis of the volumetric BMD and bone microstructure indicated that trabecular bone mainly contributed to the positive association between protein intakes and bone strength. Conclusions: These results, which were recorded in a very homogeneous population of healthy postmenopausal women, indicate that there is a beneficial effect of animal and dairy protein intakes on bone strength and microstructure. Specifically, there is a positive association between the bone failure load and stiffness of the peripheral skeleton and dietary protein intake, which is mainly related to changes in the trabecular microstructure. This trial was registered at www.controlled-trials.com as ISRCTN11865958.